2011
DOI: 10.1088/0953-4075/45/1/015502
|View full text |Cite
|
Sign up to set email alerts
|

The f-deformed Jaynes–Cummings model and its nonlinear coherent states

Abstract: Based on the f-oscillator formalism, we introduce a nonlinear Jaynes-Cummings model (NJCM) which is constructed from the standard JCM by deforming the single-mode field operators. Such a generalization of the JCM describes the interaction of a two-level atom with a single mode of the electromagnetic field in the presence of a nonlinear Kerr-like medium. Since the medium is modelled as an f-oscillator, it is possible to consider the field f-coherent states (nonlinear coherent states) and their evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…Conversely, the substitution of (24) into the left hand side of the first eq. (9) gives (27) and into the left hand side of the first eq. (10)…”
Section: It Means That (13) In General Does Not Imply (8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the substitution of (24) into the left hand side of the first eq. (9) gives (27) and into the left hand side of the first eq. (10)…”
Section: It Means That (13) In General Does Not Imply (8)mentioning
confidence: 99%
“…For example, the Jaynes-Cummings models in quantum optics, in parallel to deformed oscillator algebras, generated the Biedenharn-Macfarlane's [26],the f-oscillator's [27], the (p, q)-deformed versions [11] of this model. The same takes place for two-dimensional conformal fields theories induced by the Arik-Coon [29], the Biedenharn-Macfarlane [30], the (p, q) [31], the Oh-Sigh [28] deformed versions of the oscillator algebras.…”
Section: Introductionmentioning
confidence: 99%
“…Many generalizations have been proposed to modify the JCM in the literature [5,6,7,8,9,10,11,12,13]. In addition, various researches have been published to quantify the atom-field entangled states, using the standard JCM (and also the generalized JCM).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a lot of researchers have found that the ordinary creation and annihilation operators in JCM may be replaced by the q-deformed partners, namely, the q -deformed JCM21. Later on, JCM has been adopted with a Kerr nonlinearity within the framework of f -oscillator formalism22. Furthermore, the investigations of a class of shape-invariant bound state problem, which represents a two-level system, leads to the generalized JCM23.…”
mentioning
confidence: 99%
“…One of the most interesting cases which is not related to the q or f -calculus is R -deformed Heisenberg algebra (RDHA). Such generalized schemes naturally lead to the concept of para-fields and para-statistics18192021222324252627282930313233343536. The same RDHA was also used for solving the quantum mechanical Calogero model or pseudo harmonic oscillator (PHO)3738394041.…”
mentioning
confidence: 99%